Role of uterine artery doppler at 18-22 weeks in the prediction of pre-eclampsia: a prospective study - Pereira, Patricia Malini; Manjeera M., Lakshmi; Pereira, Valerie Anithra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pre-eclampsia is the most common pregnancy complication associated with serious maternal and fetal morbidity. Uterine artery Doppler reflects the impaired trophoblastic invasion of the uterine spiral arteries, which is involved in the aetiology of preeclampsia. Thus, uterine artery Doppler was proposed as a screening test for pre-eclampsia. Methods: A prospective cohort study of 100 singleton pregnancies was conducted in a tertiary centre and the study population were subjected to uterine artery Doppler study at 18-22 weeks gestation. Uterine artery Doppler indices of pulsatility index (PI), resistance index (RI) and persistence of diastolic notch was obtained and the outcome of pre-eclampsia was studied. Results: Out of 100 women, 14 women developed pre-eclampsia in which the resistance index showed a sensitivity of 21.4%, specificity of 91.8%, positive predictive value of 30% and negative predictive value of 87.7% and pulsatility index showed sensitivity of 35.7%, specificity of 90.6%, positive predictive value of 38.4% and negative predictive value of 89.6%. Diastolic notch had a sensitivity of 35.7%, specificity of 98.8%, positive predictive value of 83.3% and a negative predictive value of 90.4%. Conclusions: The high negative predictive values, indicated that women with normal Doppler velocimetry were unlikely to develop preeclampsia. Uterine artery Doppler, being non-invasive can be included during routine sonography to identify patients at risk of developing pre-eclampsia. Early, screening for pre-eclampsia will help in individualized antenatal surveillance and initiation of prophylactic therapy, early to reduce the adverse maternal and foetal complications of preeclampsia.